Ortodoksi Dalam Agama Hindu Kaharingan - L Sigai, Ervantia Restulita; Adi, Agung; Joyo, Puspo Renan (Satya Widya: Jurnal Studi Agama, 2024)
This article explores forms of orthodoxy in Kaharingan Hinduism with a focus on the role of the Besorah ritual and local cultural sustainability in Pasir Panjang Village, Central Kalimantan. The background of this research is rooted in the challenges faced in maintaining authentic religious practices amidst the influence of modernization and globalization. The purpose of the research is to analyze how the Besorah ritual serves as a means to strengthen the cultural and religious identity of the local community. The methodology used is a qualitative approach, through participatory observation and in-depth interviews with community leaders and ritual participants. The results show that the Besorah ritual is not just a religious practice, but also a manifestation of cultural values passed down through generations, which contributes to the sustainability of local identity. The ritual strengthens community solidarity and cements the understanding of orthodoxy among Kaharingan Hindus. The conclusion of this study confirms the importance of the Besorah ritual as a tool to maintain and strengthen religious orthodoxy in the context of local cultural dynamics, and highlights the need to preserve traditional practices in the face of modern challenges.